Extending Lean Operating Limit and Reducing Emissions of Methane Spark-Ignited Engines Using a Microwave-Assisted Spark Plug. (21st August 2012) - Rapp, Vi H.; DeFilippo, Anthony; Saxena, Samveg; Chen, Jyh-Yuan; Dibble, Robert W.; Nishiyama, Atsushi; Moon, Ahsa; Ikeda, Yuji
Abstract : A microwave-assisted spark plug was used to extend the lean operating limit (lean limit) and reduce emissions of an engine burning methane-air. In-cylinder pressure data were collected at normalized air-fuel ratios of λ = 1.46, λ = 1.51, λ = 1.57, λ = 1.68, and λ = 1.75 . For each λ, microwave energy (power supplied to the magnetron per engine cycle) was varied from 0 mJ (spark discharge alone) to 1600 mJ. At lean conditions, the results showed adding microwave energy to a standard spark plug discharge increased the number of complete combustion cycles, improving engine stability as compared to spark-only operation. Addition of microwave energy also increased the indicated thermal efficiency by 4% at λ = 1.68 . At λ = 1.75, the spark discharge alone was unable to consistently ignite the air-fuel mixture, resulting in frequent misfires. Although microwave energy produced more consistent ignition than spark discharge alone at λ = 1.75, 59% of the cycles only partially burned. Overall, the microwave-assisted spark plug increased engine performance under lean operating conditions ( λ = 1.68 ) but did not affect operation at conditions closer to stoichiometric.